2017
DOI: 10.1016/j.ctro.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Prospective analysis of in vivo landmark point-based MRI geometric distortion in head and neck cancer patients scanned in immobilized radiation treatment position: Results of a prospective quality assurance protocol

Abstract: PurposeUncertainties related to geometric distortion are a major obstacle for effectively utilizing MRI in radiation oncology. We aim to quantify the geometric distortion in patient images by comparing their in-treatment position MRIs with the corresponding planning CTs, using CT as the non-distorted gold standard.MethodsTwenty-one head and neck cancer patients were imaged with MRI as part of a prospective Institutional Review Board approved study. MR images were acquired with a T2 SE sequence (0.5 × 0.5 × 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…non-immobilized) MR acquisition for radiotherapy planning. This method demonstrated superior image quality, decreased geometric distortion, and better MR-CT co-registration [10], [11]. Prior work to ours has also confirmed the feasibility of MR acquisition in the treatment position [12].…”
Section: Introductionsupporting
confidence: 64%
“…non-immobilized) MR acquisition for radiotherapy planning. This method demonstrated superior image quality, decreased geometric distortion, and better MR-CT co-registration [10], [11]. Prior work to ours has also confirmed the feasibility of MR acquisition in the treatment position [12].…”
Section: Introductionsupporting
confidence: 64%
“…In addition, tissue magnetic susceptibility differences in this region are minimal compared with the head and neck area. Mohammed et al 28 characterized MRI distortions in the head and neck region and reported distortions of less than 2 mm but did not evaluate their dosimetric impact on RTP.…”
Section: Introductionmentioning
confidence: 99%
“…Even though MRI has a certain degree of distortion, MRI may still provide higher confidence in target delineation compared with CT. Published trials showed that geometric distortion of MRI was quantified with a clinically significant error of less than 2 mm compared with gold standard CT, in radiotherapy planning applications 11 . In addition, the error caused by geometric distortion is relatively smaller compared to the high delineation error between interobservers in radiotherapy planning using CT 12‐14 .…”
Section: Discussionmentioning
confidence: 99%